Is the hardness of material harder than diamond reliable?. (1st May 2023) - Liu, Jin; Zou, Yongtao; Zhan, Guodong David; Wang, Pei; Yan, Xiaozhi; He, Duanwei; Wang, Liping
Highlights: Develop a systematic, reliable and usable criterion that could be widely accepted for hardness testing, which is of great importance in understanding the true nature of hardness. Reveal that the hardness of the testing sample is significantly overestimated when the hardness of the indenter is close to or lower than that of the sample. Demonstrate that when the indenter material is at least 18.2% harder than the testing sample, the hardness value as measured agrees with the value resulted from a genuine diamond indenter on the same material at the same load. Abstract: With the development of new synthesis methods and chemistries, a number of new superhard materials have been reported to be harder than diamond. While such materials are highly desirable due to their wide-ranging applications, there are some inherent uncertainties in the methods utilized to determine and define the hardness of such materials. In this paper, we employed the standard Vickers diamond indenter and substitute indenters with the same shape to measure the hardness of nine ceramics and superhard materials within well-defined criteria and methodology, for the assessment of consistency in the hardness testing. The findings and the developed testing method in the current study have broad implications in characterizing new and emerging superhard materials, leading to new discoveries.